Novel combination therapy with imiquimod and sorafenib for renal cell carcinoma. (27th February 2014) - Karashima, Takashi; Komatsu, Toshihiro; Niimura, Mayumi; Kawada, Chiaki; Kamada, Masayuki; Inoue, Keiji; Udaka, Keiko; Kuroda, Naoto; Shuin, Taro
<x xml:space="preserve">Abstract</x> Objectives To investigate whether the combination of the imidazoquinoline immune response modifier, imiquimod, and the multitargeted tyrosine‐kinase inhibitor, sorafenib, inhibits the growth of renal cell carcinoma in mice. Methods Female BALB/c mice were implanted subcutaneously with 2 × 105 RENCA mouse kidney cancer cells, and were treated with transcutaneously applied cream containing imiquimod and oral administrations of sorafenib beginning 5 days after implantation of the cells. Tumor incidence and burden were determined at 28 days after initiation of therapy. T cell infiltration in the tumor was determined by immunofluorescence staining with anti‐CD3‐ε and CD8‐α antibodies. Results Therapy with imiquimod, sorafenib or their combination was well tolerated. Combination therapy with imiquimod and sorafenib significantly inhibited tumor growth when compared with administration of control vehicle, imiquimod or sorafenib alone (P < 0.05). The CD3‐ and CD8‐positive T cells infiltrated into tumors to a greater degree in response to the combination therapy when compared with tumors treated with control vehicle or sorafenib alone. Conclusions Combination therapy with a tyrosine‐kinase inhibitor and an imidazoquinoline could be a promising therapeutic strategy for patients with renal cell carcinoma.